Management of the Plant Quarantine Release Certificate in the Loading and Unloading Process at PT. Ciomas Ariya Samudera - Rudiyo, Muhammad Rifqo Faqih (Maritime Park: Journal of Maritime Technology and Society, 2026)
This study aims to analyze the effectiveness of Plant Quarantine Release Certificate management in supporting the smooth loading and unloading process of dry bulk at PT Ciomas Ariya Samudera. Plant Quarantine Release Certificate are quarantine requirements that must be met for the import of plant-based feed commodities, such as soybean meal (SBM), into Indonesia. The research method used a qualitative case study approach through in-depth interviews, observations, and documentation studies of administrative and operational processes. The results show that internal Plant Quarantine Release Certificate management can be said to be effective because it has been carried out systematically through document requirement planning, implementation of procedures according to SOPs, and supervision of document storage. However, its effectiveness is still hampered by several external factors such as weather, as well as technical disruptions to the online system, so it requires revision, re-coordination, or manual alternatives so that the process is not hampered. These obstacles result in delayed loading and unloading processes, increased logistics costs, and the risk of losses for animal feed company partners. Therefore, it is necessary to increase synergy between the company and relevant agencies, strengthen integrated digital systems, and conduct regular training to improve responsiveness to policy changes.